Antibacterial and antibiofilm efficacy of k21-E in root canal disinfection. Issue 10 (October 2021) - Daood, Umer; Bapat, Ranjeet Ajit; Sidhu, Preena; Ilyas, Muhammad Sharjeel; Khan, Abdul Samad; Mak, Kit-Kay; Pichika, Mallikarjuna Rao; Nagendrababu, Venkateshbabu; Peters, Ove A.
Abstract: Objectives: The aim of the current project was to study the antimicrobial efficacy of a newly developed irrigant, k21/E against E. faecalis biofilm. Methods: Root canals were instrumented and randomly divided into the following groups: irrigation with saline, 6% NaOCl (sodium hypochlorite), 6% NaOCl + 2% CHX (Chlorhexidine), 2% CHX, 0.5% k21/E (k21 - quaternary ammonium silane) and 1% k21/E. E. faecalis were grown (3-days) (1 × 10 7  CFU mL −1 ), treated, and further cultured for 11-days. Specimens were subjected to SEM, confocal and Raman analysis and macrophage vesicles characterized along with effect of lipopolysaccharide treatment. 3T3 mouse-fibroblasts were cultured for alizarin-red with Sortase-A active sites and Schrödinger docking was performed. TEM analysis of root dentin substrate with matrix metalloproteinases profilometry was also included. A cytotoxic test analysis for cell viability was measured by absorbance of human dental pulp cells after exposure to different irrigant solutions for 24 h. The test percentages have been highlighted in Table 1. Results: Among experimental groups, irrigation with 0.5% k21/E showed phase separation revealing significant bacterial reduction and lower phenylalanine 1003 cm −1 and Amide III 1245 cm −1 intensities. Damage was observed on bacterial cell membrane after use of k21/E. No difference in exosomes distribution between control and 0.5%k21/E was observed with less TNFα (*p < 0.05) and preferential binding of SrtA. TEM images demonstrated integrated collagen fibers in control and 0.5%k21/E specimens and inner bacterial membrane damage after k21/E treatment. The k21 groups appeared to be biocompatible to the dental pulpal cells grown for 24 h. Significance: Current investigations highlight potential advantages of 0.5% k21/E as irrigation solution for root canal disinfection.